Low-protein diet for chronic kidney disease in the Caserta Local Health Unit: the SaniARP Initiative - Troncone, Chiara; Menditto, Enrica; Orlando, Valentina; Valiante, Daniela; Farina, Giuseppina; Tari, Michele Giuseppe (Farmeconomia. Health Economics and Therapeutic Pathways, 2015)
INTRODUCTION: In clinical practice, the interest in the use of low-protein food for patients suffering from chronic kidneydisease has increased. Currently, these products are not yet contemplated in the essential levels of assistance but the Italian regions deliver, low-protein food discretionally using their own funds. The Campania Region, in 2010, interrupted the distribution of these products. With the exception of Caserta which took up distribution again in 2013. OBJECTIVE: The aim of this paper is to describe an initiative put in place by Caserta which has decided to invest in prevention. MATERIALS AND METHODS: A treatment plan for the distribution designed by a team of in-house nephrologists and data are recorded using Saniarp, a web-based platform. RESULTS: In the observation period patients with a prescription of low-protein food products were 869. The mean age was 61 years. The average cost patient / month for the nutritional treatment was 59 Euro. The average cost patient / month for any type of drug was 632 Euro. In particular, 48 Euro for EPO, 277 Euro for Chelate Agents, 16 Euro for antihypertensive therapy. DISCUSSION AND CONCLUSIONS: The policy put in place by the LHU Caserta improved care of kidney patients. The results available to date are still incomplete and do not enable us to clearly assess the benefits both in clinical and economic terms which can be produced by a low-protein diet in kidney patients. In the perspective of third party payers to budget this expense it appears entirely sustainable especially in view of the fact that this dietary treatment might delay the onset of dialysis therapy and lead to lower comorbidity for the patient.